2009
DOI: 10.3109/16066350903291066
|View full text |Cite
|
Sign up to set email alerts
|

The use of the RCQ-D in patients with poly drug abuse

Abstract: Aim: The transtheoretical model is often used in substance abuse treatment planning. For polydrug abusing patients, operationalizing the stages of change is more difficult, as their readiness to change may differ depending on the substances. It was the aim of this study to investigate if the same structure of the Dutch Readiness to Change Questionnaire (RCQ-D) in a group of alcohol abusers could be found in an inpatient group of polydrug abusers for all substances. Design: For each substance, the structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Furthermore, we found that motivation for changing substance use differs for the various substances. In line with previous research (Raes et al 2010), we conclude that it is important to assess motivation for change for each substance separately.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Furthermore, we found that motivation for changing substance use differs for the various substances. In line with previous research (Raes et al 2010), we conclude that it is important to assess motivation for change for each substance separately.…”
Section: Discussionsupporting
confidence: 78%
“…In cocaine-dependent patients, all three factors of the RCQ-D loaded on the same factor, whereas in the other categories a 2-factor solution was found. Previously, Raes et al (2010) found similar results, with the factor structure in cocaine-dependent patients being of a different nature than that for other substance categories.…”
Section: Journal Of Psychoactive Drugssupporting
confidence: 82%
See 2 more Smart Citations
“…Because previous work has shown both two and three factor solutions for the RTCQ (Crackau et al, 2010; Raes et al, 2010), we first conducted a principal component analysis (PCA) of the 12 items using orthogonal (varimax) rotation forcing three and two component structures. Determination of the scale component structure was based on Kaiser's rule (i.e., eigenvalue > 1), item component loading > .4, item factorial complexity of one, and interpretability.…”
Section: Methodsmentioning
confidence: 99%